Managing risks in digital transformation : understanding the modern landscape of digital threats with the help of real-world examples and use cases /: understanding the modern landscape of digital threats with the help of real-world examples and use cases. (2023) - Kudrati, Abbas; Kumar, Shashank; Kumar, Ashish; Armstrong-Smith, Sarah
No abstract available